2018
DOI: 10.21511/imfi.15(1).2018.16
|View full text |Cite
|
Sign up to set email alerts
|

Portfolio creation using graph characteristics

Abstract: The aim of this work is by combination of the graph theory and Markowitz portfolio theory to illustrate how some graph characteristics are related to the diversification potential of individual portfolio-forming stocks. Using the graph characteristic, the vertex eccentricity, individual stocks are divided into two groups: a group of large and group of small eccentricity. Eccentricity in this context is considered to be a very suitable metric of the centrality of individual vertices. Different price histories (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…They use the minimum spanning tree method and also planar maximally filtered graph method (PFG) and construct MST and PFG networks in the US market at different time scales. Danko and Šoltés (2018) use graph characteristics as a stock-picking tool and propose a portfolio while minimizing its standard deviation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They use the minimum spanning tree method and also planar maximally filtered graph method (PFG) and construct MST and PFG networks in the US market at different time scales. Danko and Šoltés (2018) use graph characteristics as a stock-picking tool and propose a portfolio while minimizing its standard deviation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is shown that the portfolios of factors describe the information more fully due to the explicit use of input factors. Danko & Šoltés (2018) in their work proposes to form an investment portfolio based on Markowitz theory in combination with graph theory. Testing of the resulting portfolios was carried out using simulation analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The minimum spanning tree (MST) of such networks contains the least correlated stocks in its periphery in contrast to highly correlated stocks in the centre of the tree (Onnela et al, 2003). Using the Markowitz or modern portfolio theory (MPT) (Danko and Šoltés, 2018), the least correlated assets can be selected to build optimal portfolios. MSTs were also used to develop a stock market filtering method to show that the whole market can be simulated by this reduced version (Esfahanipour and Zamanzadeh, 2015).…”
Section: Introductionmentioning
confidence: 99%